The Effect of Ukrainian War on the Global Economy, Politics, and International Relations - Song, Hongjin (Transactions on Economics, Business and Management Research, 2024)
Since the invasion began at February 24th, 2022, things have changed a lot in this planet that we call home. In this paper, I will be analysing the change in the aspects of global economy, politics and International Relations. For global economy, because the sanctions for Russian fossil fuels and the SWIFT banking system, the inflation on the UK and the USA are the most significant, as well as the increased oil price in those countries. For global politics, Russia’s hard power and soft power drops dramatically because of the invasion of Ukraine and commit multiple crimes such as breaking Geneva convention and law of wars and peace. On the other hand, Ukraine will rise after the war not only because it has more flexible commanding structure, but also it received more advanced weaponry. And for International Relations, Russia will no longer be a threat since the war ends due to out of armed personnel, and modern equipment that modern warfare required, and need to spend more time to do this.